2020
DOI: 10.1029/2020gl088567
|View full text |Cite
|
Sign up to set email alerts
|

Observed Hemispheric Asymmetry in Stratospheric Transport Trends From 1994 to 2018

Abstract: Total columns of the trace gases nitric acid (HNO3) and hydrogen chloride (HCl) are sensitive to variations in the lower stratospheric age of air, a quantity that describes transport time scales in the stratosphere. Analyses of HNO3 and HCl columns from the Network for the Detection of Atmospheric Composition Change panning 77°S to 79°N have detected changes in the extratropical stratospheric transport circulation from 1994 to 2018. The HNO3 and HCl analyses combined with the age of air from a simulation using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(38 citation statements)
references
References 55 publications
8
30
0
Order By: Relevance
“…10 Since natural variability is high in polar regions and the observational period is relatively short, it is quite expected that a simple multiple regression will lead to trend estimates that are not statistically significant. Other methods for trend analysis in polar regions, such as considering seasonal trends (Solomon et al, 2016;Szeląg et al, 2020;Galytska et al, 2019) can be explored in future work. In addition, the relation of winter-spring trends with respect to the position of the polar vortex would be an interesting subject in future studies.…”
Section: Evaluation Of Regional Ozone Trendsmentioning
confidence: 99%
“…10 Since natural variability is high in polar regions and the observational period is relatively short, it is quite expected that a simple multiple regression will lead to trend estimates that are not statistically significant. Other methods for trend analysis in polar regions, such as considering seasonal trends (Solomon et al, 2016;Szeląg et al, 2020;Galytska et al, 2019) can be explored in future work. In addition, the relation of winter-spring trends with respect to the position of the polar vortex would be an interesting subject in future studies.…”
Section: Evaluation Of Regional Ozone Trendsmentioning
confidence: 99%
“…They further analyzed BDC diagnostics, that is, the position of the subtropical transport barriers (derived from observations and model outputs), the turnaround latitude, and the latitude of the meridional trace gas gradient genesis (from ERA-Interim), to conclude that a southward shift by about 5° of the tropical transport barriers could explain the observed and modeled hemispheric asymmetry in trends. Recently, Strahan et al (2020) reported on hemispheric asymmetry in trends of long-lived tracers and AoA through an analysis of longer NDACC (Network for the Detection of Atmospheric Composition Change; De Mazière et al, 2018; http://www.ndacc.org) FTIR time series of HCl and nitric acid (HNO 3 ). These results place the previously reported trends in a longer context where interhemispheric anomalies of long-lived tracers and AoA exhibit a 5-7-year period.…”
Section: Introductionmentioning
confidence: 99%
“…The reported hemispheric asymmetry in 2005-2012 in Mahieu et al (2014;HCl) and Stiller et al (2017;N 2 O and AoA) is, for example, located between a large positive interhemispheric anomaly (peaking around 2005) and a large negative one (peaking around 2011; Southern Hemisphere minus Northern Hemisphere). Finally, Strahan et al (2020) also indirectly derived AoA trends from NDACC FTIR HCl and HNO 3 interhemispheric anomalies using a CTM AoA simulation driven by MERRA-2 (National Aeronautics and Space Administration's Modern Era Retrospective-analysis for Research Applications version 2; Gelaro et al, 2017). They concluded that the Southern Hemisphere AoA is getting younger by 1 month per decade compared to that of the Northern Hemisphere for the period 1994-2018.…”
Section: Introductionmentioning
confidence: 99%
“…First, due to possible correlations between velocities and mixing ratios, products of prime terms in the zonal mean of the Reynolds decomposition of the tendency formulation of the continuity equation do not cancel out. Following Tung (1982)…”
Section: Discussionmentioning
confidence: 99%
“…2 There are other approaches than that of Tung (1982) to interpret 2-D circulation, using different approximations. Depending on the approach chosen, the calculation of effective 2-D velocities from 3-D fields involves different terms.…”
Section: Discussionmentioning
confidence: 99%